Proceedings of the 5th Symposium on Usable Privacy and Security 2009
DOI: 10.1145/1572532.1572538
|View full text |Cite
|
Sign up to set email alerts
|

A "nutrition label" for privacy

Abstract: We used an iterative design process to develop a privacy label that presents to consumers the ways organizations collect, use, and share personal information. Many surveys have shown that consumers are concerned about online privacy, yet current mechanisms to present website privacy policies have not been successful. This research addresses the present gap in the communication and understanding of privacy policies, by creating an information design that improves the visual presentation and comprehensibility of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
226
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 318 publications
(252 citation statements)
references
References 8 publications
1
226
0
Order By: Relevance
“…Research in privacy policies, financial privacy notices, and access control have all similarly shown that privacy-related concepts and terms are often not well understood by users expected to make privacy decisions [13,15,22]. No work we are currently aware of has proposed and tested alternative permissions displays, or other ways to help users select applications in Google Play, or other application markets, as we do here.…”
Section: Android Permissions and Privacy Researchmentioning
confidence: 90%
“…Research in privacy policies, financial privacy notices, and access control have all similarly shown that privacy-related concepts and terms are often not well understood by users expected to make privacy decisions [13,15,22]. No work we are currently aware of has proposed and tested alternative permissions displays, or other ways to help users select applications in Google Play, or other application markets, as we do here.…”
Section: Android Permissions and Privacy Researchmentioning
confidence: 90%
“…Research in privacy policies, financial privacy notices, and access control have all similarly shown that privacy-related concepts and terms are often not well understood by users expected to make privacy decisions [9,10,14]. Our earlier work specifically investigated how the information display of privacy policies could influence understanding, focusing on standardized formats, terms, and definitions.…”
Section: Related Workmentioning
confidence: 99%
“…The report is based on the Privacy Nutrition Label concept presented in [18], which is an approach aimed at improving the visual presentation of privacy policies to end users. The report is constructed by combining symbols and color codes to illustrate how the user's personal data will be treated.…”
Section: F Privacy Findermentioning
confidence: 99%